2007
DOI: 10.1002/ejic.200600725
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear and Polynuclear Bridged Azido–Nickel(II) Complexes: Synthesis, Structure Determination, and Magnetic Properties

Abstract: Me 6 trien = 1,1,4,7,10,10-hexamethyltriethylene tetramine} were synthesized and structurally characterized by spectroscopic techniques, X-ray crystallography, and variable-temperature magnetic measurements. In the complexes 1-3a, the ClO 4 -groups are counterions and the Ni 2+ centers are bridged by the azido ligands in an end-to-end bonding fashion. The coordination geometry around the Ni II ions is six-coordinate with a distorted octahedral environment achieved by the four N atoms of the tetradentate amines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 80 publications
1
32
0
Order By: Relevance
“…This was synthesized following the published procedures [23] and purified by chromatographing it on silica gel and elution with a 98/2 (v/ v) mixture of ethyl acetate/MeOH. 1 (1 00 -CH 2 ), 54.15 (2 00 -CH 2 ), 35.73 (3 00 -CH 2 ). The purity of pmea and pmap compounds was sufficient for subsequent complex formation.…”
Section: Materials and Physical Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was synthesized following the published procedures [23] and purified by chromatographing it on silica gel and elution with a 98/2 (v/ v) mixture of ethyl acetate/MeOH. 1 (1 00 -CH 2 ), 54.15 (2 00 -CH 2 ), 35.73 (3 00 -CH 2 ). The purity of pmea and pmap compounds was sufficient for subsequent complex formation.…”
Section: Materials and Physical Measurementsmentioning
confidence: 99%
“…Two factors can be considered here to account for this behavior; these include steric and electronic factors. In general in the bridging EO-mode, the azido-and thiocyanato-Cu(II) complexes have Cu...Cu separations in the range of 3.0-3.6 Å [1,17,18] and are >5 Å in the corresponding bridging EE-mode [1,2,16]. Structural analysis of the complexes 2, 6, and 7 where the azide and the thiocyanate anions are terminal ligands showed that the Cu...Cu separations are 4.9141(12), 8.238(2), and 5.7010(14) Å, respectively.…”
Section: [Cu 2 (L)(ncs) 4 ]á2ch 3 Cn (7)mentioning
confidence: 99%
See 2 more Smart Citations
“…The ambidentate nature of the thiocyanate anion NCS À , together with the azide ion, N 3 À and the ability of these ligands to bridge and assemble metal ions in extended network structures made these ligands to be among the most extensively studied species [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The interaction of NCS À and N 3 À with divalent metal ions have led to the construction of polynuclear and coordination polymers of diverse topology [1][2][3][4][5]7,[10][11][12][13][14][15][16][17][18] and the development of new magnetic molecular materials of different bridging-azido, and -thiocyanato bonding modes [2,3,4b,5,7,10-17].…”
Section: Introductionmentioning
confidence: 99%